(untitled) (Malay Literature, 2011)
This article is about how the West was imagined, described and reproduced by Abdullah Munshi. Thus far we have encountered descriptions of the non-Western world by the West, which includes that of the Malays by European travellers, scientists and colonial scholar-administrators. It is thus also critical to appraise knowledge of the occident from the other and an ambivalent self such as in the person Abdullah Munshi. Abdullah’s writings were journalistic and sociological in nature. The production of his writings under conditions of early colonialism has not been sufficiently studied from the perspective of self and the other, Western and non-Western. As such, this article is significantly the first of such studies on Malay intellectual history. Abdullah’s autobiography, the Hikayat Abdullah, is used to identify a form of Malay Occidentalism. In a sense, this article plays a cataloguing role indicating the scope and character of the Malay imagination of the West. It presents part of the larger study aimed at developing a framework on Malay attitudes and representations of Europe and Western civilization. Keywords: Colonialism, occidentalism, orientalism, other, printing, self